2018
DOI: 10.1111/cbdd.13361
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic amine antidepressants suppress β‐lactam resistance in methicillin‐resistant Staphylococcus aureus (MRSA) by repressing mRNA levels of key resistance genes

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is the leading cause of recurrent infections in humans including endocarditis, pneumonia, and toxic shock syndrome. Novel therapeutics to treat MRSA and other resistant bacteria are urgently needed. Adjuvant therapy, which uses a non-toxic compound to repotentiate the toxic effects of an existing antibiotic, is an attractive response to the growing resistance crisis. Herein, we describe the evaluation of structurally related, FDA-approved tricyclic amine antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Moreover, the TCA amoxapine is active against Salmonella and Y. pestis [ 54 , 71 ]. Interestingly, some TCAs and the antipsychotic thioridazine are capable to resensitize methicillin-resistant S. aureus (MRSA) to β-lactam [ 97 , 98 , 99 ]. This is relevant, as it opens the possibility to use this drug, alone or in combination with known antibiotics, to treat resistant bacteria.…”
Section: Possible Antimicrobial Activities Of Antidepressants and Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the TCA amoxapine is active against Salmonella and Y. pestis [ 54 , 71 ]. Interestingly, some TCAs and the antipsychotic thioridazine are capable to resensitize methicillin-resistant S. aureus (MRSA) to β-lactam [ 97 , 98 , 99 ]. This is relevant, as it opens the possibility to use this drug, alone or in combination with known antibiotics, to treat resistant bacteria.…”
Section: Possible Antimicrobial Activities Of Antidepressants and Antipsychoticsmentioning
confidence: 99%
“…As mentioned earlier, TCAs and thioridazine, an antipsychotic, are able to reverse the resistance of MRSA to β-lactam. It has been reported that do so, TCAs act by repressing the expression of β-lactam resistance genes, while thioridazine acts by inhibiting the expression of genes involved in cell wall biosynthesis [ 98 , 99 ].…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Examples of such activity are -lactamase inhibition, cholesterol absorption inhibition, 3a antimicrobial, 3b-d antifungal, 4 antimalarial, 5 anti-HIV, 6 anticancer, 7 anti-inflammatory, 8 antidepressant, 9 antiviral, 10 DPP-4 inhibition 11 and anticonvulsant. 12 Additionally, lactams are very important structural motifs present in several natural products such as the penicillins 1 (Figure 1), nocardicin A (7), monobactam (8), tabtoxin (9), pseurotin A (10), dysidin (11), sintokamides A-E (12), malingamide A (13), strychnine (14), adalinine (15), corydaidine (16), caprolactin A (17), isobenganamide E (18) and bengamide K (19) ( -Lactams constitute a major class of antibiotics and contribute to more than 50% of the global antibiotics market. However, due to increasing antibacterial resistance toward -lactam antibiotics, 14 the scientific community has been forced to move its focus from four-membered lactam rings to other larger-ring lactam analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Many lactam-containing compounds possess useful biological activity, specifically with three-to seven-membered-ring lactams representing some of the most important. Examples of such activity are -lactamase inhibition, cholesterol absorption inhibition, 3a antimicrobial, 3b-d antifungal, 4 antimalarial, 5 anti-HIV, 6 anticancer, 7 anti-inflammatory, 8 antidepressant, 9 antiviral, 10 DPP-4 inhibition 11 and anticonvulsant. 12 Additionally, lactams are very important structural motifs present in several natural products such as the penicillins 1 (Figure 1), nocardicin A (7), monobactam (8), tabtoxin (9), pseurotin A (10), dysidin (11), sintokamides A-E (12), malingamide A (13), strychnine (14), adalinine (15), corydaidine (16), caprolactin A (17), isobenganamide E (18) and bengamide K (19) (…”
Section: Introductionmentioning
confidence: 99%
“…4,[13][14][15] Besides their well-known antibiotic activity, [16][17][18] lactams show a large spectra of biological outcomes, with potential therapeutic applications in different elds, spanning from cancer, diabetes and infectious diseases. In fact, a number of lactam-containing compounds are reported to act as HIV-1 integrase inhibitor, 19,20 opioid receptor agonist, 21,22 as well as antitumoral, [23][24][25] anti-inammatory, 26,27 and antidepressant agents [28][29][30] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%